Дослідження основних напрямків модифікації відходів із ПВХ - Гавва, Олександр Миколайович; Захаревич, Валерій Болеславович; Масло, Микола Андрійович; Токарчук, Сергій Володимирович (My University, 2012)
Виконано аналіз відходів із ПВХ матеріалів. Встановлена необхідність модифікації відходів із ПВХ для виготовлення із них виробів побутового, технічного та будівельного призначення. Проаналізовано результати різних методів модифікації з точки зору одержання заданих фізико-механічних властивостей. Theanalysisof wastes is conducted from ПВХ of materials. The necessity of modification of wastes is educed from PVC for making from them different wares. The results of different methods of modification are analysed from the point of view of receipt of the set properties. It is set that a basic task during processing of wastes of PVC is a division of technology of modification of wastes for making of wares of the industrial and domestic setting. As a decision of such task, next works are executed: technical properties of wares are laboratory certain from PVC and their wastes after the use; the complex of experimental researches is conducted as evaluated by properties of the done and modified PVC wares; it is set that basic direction of retrofitting of wastes from PVC are introductions of additions basis of that is made by ECO.
Keywords: відходи; wastes; ПВХ матеріали; лабораторне устаткування; методи модифікування; добавки; PVC materials; laboratory equipment; methods of retrofitting; addition; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра мехатроніки та пакувальної техніки